2020
DOI: 10.2337/figshare.13222205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Processes Underlying Glycemic Deterioration in Type 2 Diabetes: An IMI DIRECT Study

Abstract: <i>Objective </i> <p>We investigated the processes underlying glycemic deterioration in type 2 diabetes (T2D). </p> <p><i>Research Design and Methods </i></p> <p>732 recently diagnosed T2D patients from the IMI-DIRECT study were extensively phenotyped over three years, including measures of insulin sensitivity (OGIS), β-cell glucose sensitivity (GS) and insulin clearance (CLIm) from mixed meal tests, liver enzymes, lipid profiles, and baseline regional f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Slow changes in insulin sensitivity in prediabetes, on the scale of a year, are consistent with findings from recently diagnosed patients with T2D from the Innovative Medicines Initiative Diabetes Research on Patient Stratification (IMI-DIRECT) study (41). Insulin sensitivity decreased by a factor of about 2 over 36 months in a subpopulation of fast progressors, and showed no change on average in the remainder 90% of the population.…”
Section: Discussionsupporting
confidence: 81%
“…Slow changes in insulin sensitivity in prediabetes, on the scale of a year, are consistent with findings from recently diagnosed patients with T2D from the Innovative Medicines Initiative Diabetes Research on Patient Stratification (IMI-DIRECT) study (41). Insulin sensitivity decreased by a factor of about 2 over 36 months in a subpopulation of fast progressors, and showed no change on average in the remainder 90% of the population.…”
Section: Discussionsupporting
confidence: 81%
“…In a paper by Zaharia et al 30 data generated by hyperinsulinemic euglycemic clamp and C‐peptide response to intravenous glucose were included in a similar cluster analysis, confirming with more sophisticated techniques the existence of the subgroups described by Ahlqvist et al 29 . The same clusters were observed by Dennis et al, 31 who used the HOMA for investigating insulin secretion and sensitivity, and by Bizzotto et al 32 who used mathematical models applied to mixed meal tests for the assessment of both insulin secretion and sensitivity.…”
Section: Discussionsupporting
confidence: 55%
“…Among other lipid species, elevated plasma triglycerides have been traditionally considered a mere consequence of obesity and insulin resistance, their negative effects being supposedly mediated by their circulating metabolites FFA. Nevertheless, large population-based studies demonstrated that high plasma triglycerides are predictive of glucose intolerance and type 2 diabetes in a dose-dependent fashion, regardless of insulin resistance and FFA [4][5][6][7][8]. Studies using a Mendelian randomization approach found associations between genetically determined hypertriglyceridemia and risk of diabetes [9,10].…”
Section: Introductionmentioning
confidence: 99%